Flexible silver-mesh electrodes with moth-eye nanostructures for transmittance enhancement by double-sided roll-to-roll nanoimprint lithography. Issue 77 (17th October 2017) - Yi, Peiyun; Zhang, Chengpeng; Peng, Linfa; Lai, Xinmin
Abstract : A double-sided R2R NIL system is established and the novel Ag-mesh electrodes with moth-eye nanostructures have been fabricated. An increase of 4.5% in transmittance has been achieved while remaining the sheet resistance at 22.8 ± 1.3 Ω sq −1 . Abstract : Transparent conductive electrodes (TCEs) are an essential component in modern optoelectronic devices, such as touch panels, LCDs, OLEDs, and solar cells. Indium tin oxide (ITO), due to low sheet resistance and high transmittance, is still the dominant material for TCEs. However, its brittle nature and high cost hinder its future application in flexible devices, e.g., flexible displays, thin film solar cells, E-paper. Recently, patterned Ag-meshes have attracted wide attention from both academia and industry due to their excellent conductivity. Nevertheless, the transmittance is determined by gap area and restricts the further improvement of conductivity. This study proposes a novel approach to enhance the transmittance of Ag-mesh electrodes by moth-eye nanostructures which can be fabricated by double-sided roll-to-roll (R2R) nanoimprint lithography (NIL) simultaneously. Nickel mold and Anodic Aluminum Oxide (AAO) mold are developed for Ag-mesh girds and moth-eye nanostructures, respectively. A double-sided R2R NIL system is established and the novel Ag-mesh electrodes with moth-eye nanostructures have been fabricated. Sheet resistance, transmittance and flexibility performance have been evaluated systematically. An increase of 4.5% in transmittance has been achieved at a wavelength of 550 nm while remaining the sheet resistance at 22.8 ± 1.3 Ω sq −1 . This research might provide a new approach for the large-scale and high through-output fabrication of high-transparency flexible Ag-mesh electrodes.